Dynamics of endemic virus re-emergence in children in the USA following the COVID-19 pandemic (2022–23): a prospective, multicentre, longitudinal, immunoepidemiological surveillance study - Nguyen-Tran, Hai; Park, Sang Woo; Vogt, Matthew R; Permaul, Perdita; Spaulding, Alicen B; Hernandez, Michelle L; Bohl, Jennifer A; Godbole, Sucheta; Ruckwardt, Tracy J; Krug, Peter W; Moss, Daniel L; Derrien-Colemyn, Alexandrine; et al. (The Lancet infectious diseases, 2025)
The Pandemic Response Repository through Microbial and Immune Surveillance and Epidemiology (PREMISE) programme was established to translate knowledge gained from global immunoepidemiological surveillance into a better understanding of population-level dynamics of emerging and re-emerging infections, as well as into the discovery and development of biomedical countermeasures against potential pandemic threats. As proof of principle for this approach, we conducted a longitudinal immunoepidemiological study in children in the USA, focusing on enterovirus D68 (EV-D68) infection dynamics but also capturing surveillance of a broad array of other endemic respiratory pathogens. Serendipitously, our sampling spanned the lifting of widespread COVID-19 non-pharmaceutical interventions (NPIs) in 2022–23, following a unique period during which virus exposure markedly diminished. This prospective, multicentre, longitudinal, immunoepidemiological surveillance study enrolled children aged 10 years or younger and weighing at least 8 kg at three US university sites. Blood specimens collected from January to June, 2022 (visit 1; pre-enterovirus season), and from January to June, 2023 (visit 3; post-enterovirus season), were tested in a multiplex assay for antibody binding to EV-D68 (prespecified primary objective) and a panel of 15 other respiratory viruses (exploratory objectives), and for neutralising activity against EV-D68, enterovirus A71, and respiratory syncytial virus (RSV; for antibody binding assay validation). Respiratory mid-turbinate swabs collected from children with symptomatic illness who participated in symptom surveys during July–December, 2022 (visit 2; enterovirus season), underwent metagenomic sequencing for pathogen detection. Serological data for EV-D68 were incorporated into epidemiological models based on case data from national surveillance to predict future transmission dynamics. Of 488 eligible children approached, 174, with a median age of 3·4 years (IQR 1·9–6·4), were enrolled and followed up longitudinally from January, 2022, to June, 2023. Three children withdrew before study completion and 51 were lost to follow-up between visits 1 and 3. 90 paired serological samples and 73 respiratory swabs were tested. Mean antibody binding and neutralisation titres against all viruses tested increased over the study period, most notably in younger children with lower initial titres. The highest exposure rates (seroconversion or antibody boosting) were seen with SARS-CoV-2 (51 [59%] of 87), EV-D68 (36 [41%] of 87), RSV (36 [41%] of 87), and influenza (35 [40%] of 87), whereas the pathogens most frequently detected by respiratory swab sequencing were EV-D68 (clade B3), rhinovirus A, and rhinovirus C (n=7 each). Incorporating EV-D68 serological data into epidemiological models resulted in an 82% reduction in the range of prediction errors and a 33% reduction in median prediction errors for longer-term EV-D68 circulation dynamics compared with national pathogen surveillance data alone. In this study, we captured immunological evidence of endemic virus re-emergence in children following lifting of pandemic NPIs, which revealed high rates of exposure to endemic respiratory pathogens in a large group of seronegative, predominantly younger, children. This study demonstrates the feasibility and utility of immunoepidemiological surveillance to enable more precise and accurate modelling of pathogen circulation dynamics to predict and prepare for future waves of disease. Intramural Research Program of the National Institute of Allergy and Infectious Diseases–Vaccine Research Center, and the National Cancer Institute, National Institutes of Health.